Learning Poverty in the Time of COVID-19 : A Crisis within a Crisis - Azevedo, Joao Pedro (World Bank, Washington, DC, 2020)
This brief summarizes the results of simulations estimating the potential impacts of the COVID-19 pandemic in learning poverty. Of 720 million primary school age children, 382 million are learning poor, either out of school or below the minimum proficiency level in reading. COVID-19 could boost that number by an additional 72 million to 454 million. In a post-COVID-19 scenario of no remediation and low mitigation effectiveness for the effects of school closures, simulations show learning poverty increasing from 53 percent of primary-school-age children to 63 percent.